Merging of Opinions under Uncertainty - Monika Bier; Daniel Engelage (University of Bonn, Bonn Graduate School of Economics (BGSE), 2010)
We consider long-run behavior of agents assessing risk in terms of dynamic convex risk measures or, equivalently, utility in terms of dynamic variational preferences in an uncertain setting. By virtue of a robust representation, we show that all uncertainty is revealed in the limit and agents behave as expected utility maximizer under the true underlying distribution regardless of their initial risk anticipation. In particular, risk assessments of distinct agents converge. This result is a generalization of the fundamental Blackwell-Dubins Theorem, cp. [Blackwell & Dubins, 62], to convex risk. We furthermore show the result to hold in a non -time-consistent environment.
Keywords: C61; C65; D81; 330; Dynamic Convex Risk Measures; Multiple Priors; Uncertainty; Robust Representation; Time-Consistency; Blackwell-Dubins; Risikopräferenz; Erwartungstheorie; Entscheidung bei Unsicherheit; Zeitkonsistenz; Erwartungsnutzen; Theorie